Mengembangkan Potensi Multiple Intelligences Siswa SD melalui Kurikulum Deep Learning - Abd. Rahman Saleh; Salmiah (FKIP UNSULTRA, 2025)
This study is a literature study that aims to analyze how deep learning curriculum can be used to develop the potential of multiple intelligences in elementary school students. Multiple intelligences or multiple intelligences proposed by Howard Gardner include eight types of intelligence, namely linguistic, logical-mathematical, spatial, musical, kinesthetic, interpersonal, intrapersonal, and naturalist. In the context of elementary education, it is important for teachers to not only focus on academic intelligence, but also accommodate the various forms of intelligence possessed by students. The deep learning curriculum focuses on in-depth, meaningful, and learner-centered learning. This approach supports the development of multiple intelligences because it provides space for students to actively explore their interests, talents, and learning styles. This study analyzed 20 national and international journals published in the last five years that are relevant to the topic. The results of the study show that the implementation of the deep learning curriculum through contextual, project-based, and collaborative learning can facilitate the development of various intelligences in elementary school students. This curriculum also requires the role of teachers as facilitators who are able to design different learning strategies according to student characteristics. This study recommends the need for teacher training and the preparation of deep learning-based teaching tools that are adaptive to the diversity of children's intelligence.